EFFECTS OF COMMERCIAL ACTIVITIES ON LIVABILITY IN URBAN CENTRES: THE CASE OF OJA OBA, ADO -EKITI, NIGERIA. - OLOWOOKERE, Clement Adebayo & ALA, Adebayo Ayodeji (International Journal of Research Science and Management, 2018)
Commercial activity is conceived as a demonstration of exchange or conduct of business exercises in form of selling, dealing and shopping, either on a general course or a specific exchange that might be on the substantial or little scale. Urban areas assume a critical part of human life since many people want to live, work and recreate in the city. The idea makes novel settings for any community to develop in a more supportable manner. In the perspective of this, this paper examined the effect of commercial activities on city bearableness around Oja Oba focal market, in Ado Ekiti, Ekiti State. The study centers on the kinds of commercial activities in the study area versus the socio-economic characteristics of the occupants. The research makes utilization of questionnaires and individual perception to get required data. Discoveries uncovered that adolescents and grown-ups are associated with commercial activities like road exchanging/street trading, selling and pushing of wheel dump cart. It also reveals the poor condition of some fundamental facilities which constitute havocs to the study area which, much of the time, degrade the aesthetics looks of the environment and poses genuine dangers to human livability and supportability of facilities provided. The study prescribes, in addition to other things, the provision of more market-shops and stalls at moderate cost, the annihilation of merchandise display at the center of the road, the provision of health facilities, roads restoration, as well as provision of waste disposal to militate the observed issues.